Managerial Competency Model for the Management of Equality Educational Institutions in the Global Era - Qonita Rahmi; Heru Santosa; Siti Zulaikha (STAI Hubbulwathan Duri, 2021)
This study aims to determine managerial competencies for management of Equality Education Institutions in Tangerang relevant to the current global era. Competent managers have an impact on the quality of education. This study was qualitative research with quantitative descriptive methods. Collecting data used observation, interview, documentation, and questionnaire. Analysis data had four steps were data collection, data reduction, data display and data analysis. The finding concluded that managerial competency must be increased to identify problems and institutional needs, build a quality learning climate and system, program evaluation models are not regular. There is no follow-up on the results of program supervision. In addition, managerial competence must also use technological devices with various advances useful in managing educational institutions.